Autophagy and Listeria monocytogenes : the role(s) of cargo receptors - Singh, Madhu; Justus Liebig University Giessen (My University, 2014)
The data presented in this study shed light on the involvement of all the known five autophagy cargo receptors (also known as autophagy adaptors) i.e. SQSTM1, NDP52, OPTN, NBR1 and TAX1BP1, in mediating the restriction of the intracellular growth of L. monocytogenes. The involvement of the three autophagy adaptors: OPTN, NBR1 and TAX1BP1, previously unknown to link L. monocytogenes to the autophagosomal membrane, has been identified. The phosphorylation of OPTN by TBK1 was essential for the growth restriction of L. monocytogenes. NBR1 seems to be the most important autophagy cargo receptor for L. monocytogenes, as it was the only one to restrict the growth of both Lm EGD-e and Lm?actA2. NBR1 knockdown also resulted in the highest increase in the intracellular growth of Lm EGD-e (2.9-fold) and Lm?actA2 (1.9-fold), as compared to the other cargo receptors. With the exception of NBR1, the absence of all the other autophagy cargo receptors: OPTN, SQSTM1, NDP52 and TAX1BP1, only led to increased intracellular loads of Lm EGD-e, but not those of Lm?actA2. Because of its inability to move within the host cell cytosol after its escape from the phagosomal compartment, Lm?actA is much more ubiquitinated than Lm EGD-e. This may lead to the simultaneous binding of several autophagy cargo receptors to Lm?actA, thereby linking it to the autophagosomal membrane for its subsequent degradation. Lm EGD-e, on the other hand, is capable of intracellular movement by means of the ActA protein. It is, therefore, susceptible to autophagy at different stages, like at the time of multiplication in the cytoplasm, or while entering from one cell to the other, and all the five known autophagy adaptors are capable of recruiting it to the autophagosome. A part of the population of Lm EGD-e that is free in the cytoplasm is targeted by autophagy, while another part of this population forms an actin tail and moves from one cell to the other.

Die Daten in dieser Studie geben Aufschluss über die Beteiligung aller fünf bekannten Autophagie-Cargo-Rezeptoren (auch als Autophagie-Rezeptoren bezeichnet), d.h. SQSTM1, NDP52, OPTN, NBR1 und TAX1BP1, bei der Einschränkung des intrazellulären Wachstums von L. monocytogenes. Die Mitwirkung der drei Autophagie-Rezeptoren OPTN, NBR1 und TAX1BP1 bei der Bindung von L. monocytogenes an die Autophagosomen-Membran wurde hier erstmals beschrieben. Die Phosphorylierung von OPTN durch TBK1 ist hierbei von entscheidender Bedeutung für die Wachstumsrestriktion von L. monocytogenes. NBR1 übernimmt wahrscheinlich die Hauptfunktion als Autophagie-Rezeptor für L. monocytogenes, da er sowohl das Wachstum von Lm EGD-e als auch von Lm?actA2 einschränkt. Der knock-down von NBR1 mit siRNA führte zur höchsten Zunahme des intrazellulären Wachstums von Lm EGD-e (2,9-fach) und Lm?actA2 (1,9-fach) im Vergleich zum knock-down aller anderen Autophagie-Rezeptoren. Im Gegensatz zu NBR1 führte der knock-down aller anderen Autophagie-Rezeptoren nur zu einer Zunahme des Wachstums von Lm EGD-e, aber nicht von Lm?actA2. Da sich Lm?actA2 nach seiner Freisetzung aus dem Phagosom nicht bewegen kann, ist es im Vergleich zu Lm EGD-e viel stärker ubiquitiniert. Das erlaubt die gleichzeitige Bindung mehrerer Autophagie-Rezeptoren an Lm?actA2 mit anschließender Kopplung an die Autophagosomen-Membran und bakteriellen Abbau. Im Gegensatz zu Lm?actA2 kann sich Lm EGD-e mit Hilfe des ActA Proteins intrazellulär bewegen. Es ist deshalb zu verschiedenen Zeitpunkten anfällig für Autophagie: bei der Vermehrung im Zytoplasma oder beim Befall der nächsten Wirtszelle. Alle fünf Autophagie-Rezeptoren können die ubiquitinierten Bakterien an das Autophagosom koppeln. Ein freibeweglicher Anteil von Lm EGD-e wird im Zytoplasma gezielt durch Autophagie beseitigt, während andere Lm EGD-e Bakterien einen Aktin-Schwanz bilden und die nächste Zelle infizieren.
Autophagie und Listeria monocytogenes : die Rolle der Autophagie-Cargo-Rezeptoren
Keywords: Listeria monocytogenes; Autophagie; Cargo-Rezeptoren; Listeria monocytogenes; autophagy; cargo receptors; ddc:610